The Role of Law in Combating Criminal Acts of Corruption - Samsidar Samsidar (PT. Anagata Sembagi Education, 2024)
Corruption is a crucial problem that hampers national development and undermines public trust in the government. This article discusses the role of law in combating corruption in Indonesia. Through a qualitative approach, this study explores the effectiveness of legal instruments, institutions, and challenges in their implementation. Law has a strategic function as a tool of social control and a repressive mechanism to provide a deterrent effect to perpetrators of corruption. However, bureaucratic complexity, weak law enforcement, and a permissive culture towards corruption are still major obstacles. The discussion of the article focuses on the role of anti-corruption laws, law enforcement institutions such as the KPK, and the influence of legal reform in strengthening integrity and accountability. This study concludes that although there has been progress in legal instruments and institutions, the role of law has not been maximized without political commitment and public participation. Therefore, collaboration between legal actors and civil society elements is crucial to creating an effective anti-corruption system.